Preliminary Study of MT-ATP6 Gene’s Alterations in Patients with Breast Cancer in Vietnam - Thi Tu Linh, Nguyen; Thao, Nguyen Thi; Dung, Do Thi; Thai, Trinh Hong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2DO - 10.25073/2588-1132/vnumps.4087, 2017)
The MT-ATP6 gene encodes for a protein subunit which is central to the proton channel of the ATP synthase. Mutations of MT-ATP6 gene can affect the ATP synthesis and may play an important role in the process of tumorigenesis. The purpose of this study was to identify potential changes of MT-ATP6 gene in pair of tumor and adjacent tissues of 102 patients with breast cancer and in blood samples of 65 controls by using direct DNA sequencing and PCR-RFLP method. Then, statistical analysis was used to analyze the association between some typical changes and pathological features of breast cancer. As a result, 20 changes in the MT-ATP6 gene in 35 examined breast cancer tissues and 13 changes in 26 blood control samples were reported, of which 12 alterations altered the amino acid and a variant, 9183insC, had not been described in the literature so far. Most of the variants had low frequencies from 2.86% to 5.71%. Two variants, G9053A and G8584A, which changed the amino acid sequence and had high frequency, were screened in all samples. Our results indicated that the frequencies of G9053A and G8584A were 21,6% (22/102 cases) and 24,5% (25/102 cases) respectively in tissues of breast cancer patients and 18,5% (12/65 cases) in normal blood controls. However, there was no statistically significant difference in G9053A and G8485A rates between breast cancer patients and controls as well as between mtDNA alterations and the pathological features of breast cancer such as age, size of tumors, number of lymph nodes, size of lymph nodes, T stage, N stage, tumor differentiation and stages of disease. This study showed that the variations of MT-ATP6 gene differed from patient groups. In Vietnamese patients with breast cancer, the rates of G9053A and G8485A were relatively high but these changes were not statistically related to breast cancer.